Tanaman Transgenik dan Kebijakan Pengembangannya di Indonesia - Faisal Faisal (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
Transgenics plant is a plant that is produced by genetic engineering process. This product still creates polemic, because its impact still not certain yet, for human and environment. European countries seem to be careful in distributing or to importing this product, but United State actively promote and produce this plant. In order to develop and to protect it's country, US has prepared regulations, policy and institutions. Regulation should be prepared in Indonesia, as well as policies and institutions, because this product has been distributed and consumed largely. In addition, this regulations and policy are important for research activities. This review discusses about transgenic development, and government policies for the development of transgenics technology in Indonesia.